Understanding the association of Future Time Perspective (FTP) and planning for retirement - Dayang Kartini, Abang Ibrahim; Nor Wahiza, Abdul Wahat (2014)
This is a conceptual paper to review the needs of Future Time Perspective (FTP) in planning for retirement. Individuals’ future time perspective might influence their choices and goals regarding short term or long term planning. Future time perspective is an important factor when planning about the importance of retirement. However, little is known about the relationship between FTP of employees and planning for retirement. The paper aims to examine the relationship between FTP and planning for retirement. The paper was guided by the theory of goal-setting. The paper ends with recommendations of few factors that need to be considered for future investigations.